2019
DOI: 10.1111/jan.14186
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evidence syntheses: Assessing the relative contributions of multi‐context and single‐context reviews

Abstract: Aims To examine the strengths and weaknesses of multi‐context (international) qualitative evidence syntheses in comparison with single‐context (typically single‐country) reviews. We compare a multi‐country synthesis with single‐context syntheses on facility‐based delivery in Nigeria and Kenya. Design Discussion paper. Background Qualitative evidence increasingly contributes to decision‐making. International organizations commission multi‐context reviews of qualitative evidence to gain a comprehensive picture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This review privileges countries of direct applicability to a UK context. The merits of multi‐context and single‐context syntheses have been debated elsewhere (Booth, Mshelia, Analo, & Nyakang'o, 2019). Excluded studies from countries such as Switzerland (Zuniga et al, 2015) and Belgium might have contributed further data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review privileges countries of direct applicability to a UK context. The merits of multi‐context and single‐context syntheses have been debated elsewhere (Booth, Mshelia, Analo, & Nyakang'o, 2019). Excluded studies from countries such as Switzerland (Zuniga et al, 2015) and Belgium might have contributed further data.…”
Section: Discussionmentioning
confidence: 99%
“…This review privileges countries of direct applicability to a UK context. The merits of multi-context and single-context syntheses have been debated elsewhere (Booth, Mshelia, Analo, & Nyakang'o, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…with included studies from multiple countries). 11 One methodological concern is that multi-context reviews access a fraction of relevant evidence. The multi-context review 4 , a high-quality qualitative synthesis, only identified 2 studies from Nigeria.…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 99%
“…This review employed the multi-context approach to synthesize data, providing a wide range of evidence that allows cross-setting comparison and applying study findings to broader settings [47,48]. Although such an approach offers transferable patterns of findings at a global level, they may be too general to target important local characteristics or audiences, leading to the study overlooking the relevance of specific contexts and blurring critical differences across different studies [47,48]. It might also appear that the study is ignoring the significance of context in evidence synthesis [48].…”
Section: Strengths and Limitationsmentioning
confidence: 99%